Analysis of microplastics in water by micro-Raman spectroscopy: Release of plastic particles from different packaging into mineral water - Schymanski, Darena; Goldbeck, Christophe; Humpf, Hans-Ulrich; Fürst, Peter (Water research (Oxford), 2018)
Microplastics are anthropogenic contaminants which have been found in oceans, lakes and rivers. Investigations focusing on drinking water are rare and studies have mainly been using micro-Fourier Transform Infrared Spectroscopy (μ-FT-IR). A major limitation of this technique is its inability to detect particles smaller than 20 μm. However, micro-Raman spectroscopy is capable of detecting even smaller particle sizes. Therefore, we show that this technique, which was used in this study, is particularly useful in detecting microplastics in drinking water where particle sizes are in the low micrometer range. In our study, we compared the results from drinking water distributed in plastic bottles, glass bottles and beverage cartons. We tested the microplastic content of water from 22 different returnable and single-use plastic bottles, 3 beverage cartons and 9 glass bottles obtained from grocery stores in Germany. Small (–50-500 μm) and very small (1–50 μm) microplastic fragments were found in every type of water. Interestingly, almost 80% of all microplastic particles found had a particle size between 5 and 20 μm and were therefore not detectable by the analytical techniques used in previous studies. The average microplastics content was 118 ± 88 particles/l in returnable, but only 14 ± 14 particles/l in single-use plastic bottles. The microplastics content in the beverage cartons was only 11 ± 8 particles/l. Contrary to our assumptions we found high amounts of plastic particles in some of the glass bottled waters (range 0–253 particles/l, mean 50 ± 52 particles/l). A statistically significant difference from the blank value (14 ± 13) to the investigated packaging types could only be shown comparing to the returnable bottles (p < 0.05). Most of the particles in water from returnable plastic bottles were identified as consisting of polyester (primary polyethylene terephthalate PET, 84%) and polypropylene (PP; 7%). This is not surprising since the bottles are made of PET and the caps are made of PP. In water from single-use plastic bottles only a few micro-PET-particles have been found. In the water from beverage cartons and also from glass bottles, microplastic particles other than PET were found, for example polyethylene or polyolefins. This can be explained by the fact that beverage cartons are coated with polyethylene foils and caps are treated with lubricants. Therefore, these findings indicate that the packaging itself may release microparticles. The main fraction of the microplastic particles identified are of very small size with dimensions less than 20 μm, which is not detectable with the μ-FT-IR technique used in previous studies. [Display omitted] •38 mineral waters were analyzed for microplastics by means of μ-Raman spectroscopy.•Microplastics were found in every type of water, almost 80% are sized between 5 and 20 μm.•Statistically significant difference from blank value could only be proven towards returnable bottles.•The found particles correlated with the materials the bottles/cartons were made of.•This indicates that plastic packaging emit microparticles, ingested directly by consumers.